2023
DOI: 10.1021/acsenergylett.3c00385
|View full text |Cite
|
Sign up to set email alerts
|

Diminishing Space-Charge Layer Effect of Zinc Anodes by an Anion-Immobilized Electrolyte Membrane

Abstract: The Zn dendrite issue, which is closely related to the creation of the space-charge region upon local anion depletion during cycling, has plagued the practical applications of aqueous Zn metal batteries (ZMBs). Herein, we propose a Kevlar-derived hydrogel (KevlarH) electrolyte with immobilized anions to diminish the space-charge layer effect. SO 4 2− anions are strongly tethered to amide groups of polymer chains, which mitigates the concentration polarization of interfacial Zn 2+ ions by preventing the anion d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 60 publications
2
10
0
Order By: Relevance
“…This kinetic result indicated that the Zn-CCS polymer crowding layer exhibited the function of repelling anions (I 3 – and SO 4 2– ) and accelerating the desolvation of [Zn­(H 2 O) 6 ] 2+ . In addition, the normalized density of Zn 2+ was significantly higher at the Zn interface, which was consistent with the properties of the Zn-CCS interface layer (Figure h) . Finally, the charging and discharging process of Zn-CCS||I 2 /AC was observed by in situ Raman which could detect the distribution of iodide on the surface of the zinc anode in real time.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…This kinetic result indicated that the Zn-CCS polymer crowding layer exhibited the function of repelling anions (I 3 – and SO 4 2– ) and accelerating the desolvation of [Zn­(H 2 O) 6 ] 2+ . In addition, the normalized density of Zn 2+ was significantly higher at the Zn interface, which was consistent with the properties of the Zn-CCS interface layer (Figure h) . Finally, the charging and discharging process of Zn-CCS||I 2 /AC was observed by in situ Raman which could detect the distribution of iodide on the surface of the zinc anode in real time.…”
Section: Resultssupporting
confidence: 79%
“…In addition, the normalized density of Zn 2+ was significantly higher at the Zn interface, which was consistent with the properties of the Zn-CCS interface layer (Figure 5h). 65 Finally, the charging and discharging process of Zn-CCS||I 2 /AC was observed by in situ Raman which could detect the distribution of iodide on the surface of the zinc anode in real time. Only the weak signal of I 3…”
Section: Resultsmentioning
confidence: 99%
“…The coupling of anions to cations reduces the free ion concentration and lowers the conductivity, and the movement of the anions themselves also reduces the proportion of Zn 2+ -ion migration in the total conductance (Zn 2+ -ion transfer number). Thus, it is the attraction of the wet strength agent to SO 4 2– that allows the SO 4 2– anion to be linked to the polymer and immobilized in the WSFP separator. This not only mitigates the concentration polarization of the Zn 2+ ions at the interface by preventing anion depletion but also increases the Zn 2+ -ion transference number . The schematic diagram demonstrates the influence of WSFP and the FP separator on the transport and diffusion of Zn 2+ and SO 4 2– , as displayed in Figure f.…”
mentioning
confidence: 93%
“…It is clear that the cell with WSFP has a lower resistance at all tested temperatures, indicating faster ion transport in the AZIBs (Figure S4a–c). Besides, the curve fitted according to the Arrhenius equation ( ) in Figure b shows that the cell with WSFP delivers a lower desolvation barrier (42.07 kJ mol –1 ) than the battery with GF (44.1 kJ mol –1 ) and FP separator (46 kJ mol –1 ), indicating an improved capability of desolvation of the (Zn­(H 2 O) 6 ) 2+ . , Moreover, the Zn 2+ transference number with different separators were measured by using a chronoamperometry (CA) method at a constant polarization potential of 10 mV (Figure S5a,b). Compared with the Zn 2+ -ion transference number of 0.322 for the cell with the GF separator, the Zn 2+ -ion number of the battery with the WSFP separator is higher, reaching 0.79, as shown in Figure c.…”
mentioning
confidence: 99%
“…Highly concentrated electrolytes have been substantiated to weaken the solvation interaction between Zn 2+ and H 2 O in the electrolyte by breaking the hydrogen bond (H-bond) network in spite of the high cost, which inspires the widespread exploitation of various inorganic and organic additives. [20][21][22][23][24][25][26][27][28][29][30][31][32][33] The introduction of these additives can usually tailor the Zn 2+ solvation sheath, accelerate the de-solvation process and readily construct an electrode/electrolyte interface owing to the strong attraction with Zn meal. [34][35][36][37][38][39][40][41][42] Therefore, the Zn 2+ flux can be efficiently regulated to a certain extent, thus leading to a dendrite-free and non-corrosive Zn deposition.…”
Section: Introductionmentioning
confidence: 99%